2021
DOI: 10.1126/science.abg5268
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent, protective, and convergent IgG recognition of SARS-CoV-2 non-RBD spike epitopes

Abstract: The molecular composition and binding epitopes of the immunoglobulin G (IgG) antibodies that circulate in blood plasma after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are unknown. Proteomic deconvolution of the IgG repertoire to the spike glycoprotein in convalescent subjects revealed that the response is directed predominantly (>80%) against epitopes residing outside the receptor binding domain (RBD). In one subject, just four IgG lineages accounted for 93.5% of the response, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
170
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(187 citation statements)
references
References 53 publications
16
170
1
Order By: Relevance
“…Neutralizing antibodies also target non-RBD Spike epitopes, particularly in the NTD 26 . The role of the NTD during viral entry is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralizing antibodies also target non-RBD Spike epitopes, particularly in the NTD 26 . The role of the NTD during viral entry is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed to recognize sugar moieties upon initial binding and might be involved in pre-fusion to post-fusion transition of the Spike 27 . Some mAbs targeting the NTD may exhibit high neutralization potency without preventing Spike binding to ACE2 26,27 . These non-RBD antibodies are highly prevalent and may represent more than 80% of the anti-Spike IgG response, even if 90% of the neutralizing activity targets the RBD 17,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic hypermutation has also been shown to occur at extrafollicular sites during both infection and chronic autoimmunity (78-80), and LN-Th1 cells could therefore help select B cells that acquire affinity-increasing BCR mutations. Alternatively, multiple studies have identified potent, neutralizing antibodies with minimal somatic hypermutation from COVID-19 patients, suggesting that the naïve repertoire in humans already harbors protective antibodies that do not require additional affinity maturation (81)(82)(83)(84)(85)(86)(87)(88)(89). Mice may also possess near-germline antibodies with high affinity to SARS-CoV-2, and therefore the role of LN-Th1 cells in this case would be to select and expand the B cells expressing these sequences.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is Although the most potent SARS-CoV-2 nAbs target the RBD (12,13,(15)(16)(17)(18)(19)(20), recent antibody profiling efforts and the emergence of multiple VOC with mutations in the NTD that affect the efficacy of nAbs suggesting that NTD-directed antibodies are important for effective control of virus infection (22)(23)(24)41). Therefore, we tested if COVID-19 convalescent sera-mediated neutralization of rVSV-SARS2 is altered by .…”
Section: Epitope Mapping Of the Most Potent Rbd And Ntd Mabsmentioning
confidence: 99%